American music writing: an unruly history. Issue 3 (December 2021) - Weisbard, Eric
Abstract: Popular music writing has made for strange colleagues and quickly lost legacies. I want to sketch some of them and suggest how they continue to influence the US version of popular music studies, arguably more so in our moment than in the previous period that codified an academic approach. I'll be anecdotal, alive to particulars of language, affiliation, method and form rather than attempting a quantification. Ranging from William Billings in 1770 to Daphne Brooks in 2021, I'll explore how such key framings as vernacular, sentimental and literary have shaped the nature of books on song. My hope is that, in synthesizing the larger history, I can suggest why so often this work could be characterized as, to use one of Robert Palmer's favourite words, unruly.